Feasibility of Video-Assisted Thoracoscopic Surgery via Subxiphoid Approach in Anterior Mediastinal Surgery: A Meta-Analysis - Luo, Yuxiang; He, Feng; Wu, Qingchen; Shi, Haoming; Chen, Dan; Tie, Hongtao (Frontiers in Surgery, 2022)
Background: Accumulating researches show potential advantages of video-assisted thoracoscopic surgery (VATS) via the subxiphoid approach, and this meta-analysis aims to investigate the efficacy and safety of the subxiphoid approach for anterior mediastinal surgery. Methods: Relevant studies were retrieved by searching Embase and PubMed databases (from the inception to Oct 1, 2021). Primary outcomes included postoperative pain, intraoperative blood loss, operation time, chest tube duration, and hospital length of stay. All meta-analyses were performed by using random-effects models. Results: Overall, fourteen studies with 1279 patients were included, with 504 patients undergoing anterior mediastinal surgery via subxiphoid approach and 775 via other approaches. The pooled results indicated that the subxiphoid approach was associated with reduced postoperative pain indicated by visual analog scale (Weight mean difference (WMD): 24 hours: -2.27, 95% CI: -2.88 to -1.65, P < 0.001; 48-72 hours: -1.87, 95% CI: -2.53 to -1.20, P < 0.001; 7 days: -0.98, 95% CI: -1.35 to -0.61, P < 0.001), shortened duration of chest tube drainage (WMD: -0.56 days, 95% CI: -0.82 to -0.29, P < 0.001), shortened hospital length of stay (WMD: -1.46 days, 95% CI: -2.28 to -0.64, P < 0.001), and reduced intraoperative blood loss (WMD: -26.44 ml, 95% CI: -40.21 to -12.66, P < 0.001) by comparison with other approaches in anterior mediastinal surgery. Besides, it has no impact on operation time and the incidence of complications of transition to thoracotomy, postoperative pleural effusion, phrenic nerve palsy, and lung infection. Conclusions: Our study suggests that the subxiphoid approach is a feasible alternative approach and even can be a better option for anterior mediastinal surgery. Further large-scale multicenter randomized controlled trials are needed to validate this finding.